A "flexible" carborane-cored luminogen: variable emission behaviours in aggregates. Issue 23 (19th May 2021) - Li, Jiaxin; Xu, Jinkai; Yan, Linbo; Lu, Changsheng; Yan, Hong
Abstract : Aggregation induced photophysical properties of a "flexible" carborane-cored luminogen are presented. Abstract : The performance of tunable emissions in aggregates is highly desirable but challenging owing to the restricted molecular conformations of luminogens. Herein, we designed and synthesized a new "flexible" luminogen, a carborane-cored compound NAPH, which exhibits variable photophysical behaviours in aggregates, such as aggregation-induced emission, crystallization-induced emission, polymorph-dependent emission, and mechanochromic luminescence. Moreover, the two polymorphs with different emission colors show opposite mechano-responsive luminescence, which is rarely observed for single-component luminescent materials. Both theoretical calculations and photophysical experiments reveal that the carborane-cored luminogen could afford variable conformations. This endows the whole molecule with multiple conformations in aggregates, thus leading to variable emission behaviours. Therefore, the present work provides new access to the construction of multifunctional single-component solid-state luminescent materials.